2014
DOI: 10.1016/j.jobcr.2014.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Cephalometric skeletal evaluation of patients with Incontinentia Pigmenti

Abstract: a b s t r a c tPurpose: The aim of this study was to evaluate the skeletal characteristics of patients with the rare genetic disease of Incontinentia Pigmenti, by lateral cephalometric analysis on the antero-posterior plane and by frontal cephalometric analysis on the horizontal plane.Methods: Lateral skeletal cephalometric analyses were performed according to Steiner for evaluation of antero-posterior direction, and frontal skeletal cephalometric analyses according to Ricketts for evaluation of horizontal dir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…[22][23][24][25][26] Other clinical manifestations Mammary gland complications are relatively common and constitute a minor diagnostic criterion (Table 1). Bone anomalies 27 as well as lethal forms of pulmonary hypertension have been described 28,29 often in isolated cases.…”
Section: Major Criteriamentioning
confidence: 99%
“…[22][23][24][25][26] Other clinical manifestations Mammary gland complications are relatively common and constitute a minor diagnostic criterion (Table 1). Bone anomalies 27 as well as lethal forms of pulmonary hypertension have been described 28,29 often in isolated cases.…”
Section: Major Criteriamentioning
confidence: 99%
“…Although the frequency with which PI patients present agenesis, hypodontia, and even anodontia, and skeletal class III with loss of vertical dimension has been reported in the literature [ 10 , 11 ], our patient had no missing teeth and presented a skeletal class II with an increase in the vertical dimension (ENA-Xi-Pm > 47°) and convex profile [ 10 , 11 , 12 , 13 ].…”
Section: Case Reportmentioning
confidence: 80%
“…In a coronal section, cranial asymmetry and cerebral parenchyma atrophy were observed, with marked grooves in the temporal and parietal lobes and an increase in the size of the cerebral ventricles (Figure 5). Although the frequency with which PI patients present agenesis, hypodontia, and even anodontia, and skeletal class III with loss of vertical dimension has been reported in Although the frequency with which PI patients present agenesis, hypodontia, and even anodontia, and skeletal class III with loss of vertical dimension has been reported in the literature [10,11], our patient had no missing teeth and presented a skeletal class II with an increase in the vertical dimension (ENA-Xi-Pm > 47 • ) and convex profile [10][11][12][13].…”
Section: Case Reportmentioning
confidence: 93%
See 1 more Smart Citation
“…With regard to maxillofacial morphology, Maahs et al 5) reported Class II malocclusion as the most common (44.4%), followed by Class III (33.3%), and Class I (22.2%) following cephalographic evaluation of 9 patients with Bloch-Sulzberger syndrome. However, several other reports describe development of anterior crossbite as a result of poor maxillary growth 3,9,10,16) .…”
Section: Discussionmentioning
confidence: 99%